2017
DOI: 10.1074/jbc.m116.751404
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Analyses Reveal Profound Effects of Fibroblast Growth Factor 16 as a Metabolic Regulator

Abstract: Edited by George M. CarmanThe discovery of brown adipose tissue (BAT) as a key regulator of energy expenditure has sparked interest in identifying novel soluble factors capable of activating inducible BAT (iBAT) to combat obesity. Using a high content cell-based screen, we identified fibroblast growth factor 16 (FGF16) as a potent inducer of several physical and transcriptional characteristics analogous to those of both "classical" BAT and iBAT. Overexpression of Fgf16 in vivo recapitulated several of our in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…FGF19 is mainly secreted by ileal enterocytes in response to bile acid activation of the nuclear receptor FXR, and then, FGF19 acts on the cell surface receptor complex in hepatocytes to inhibit bile acid synthesis and gluconeogenesis and stimulate glycogen protein synthesis [ 48 ]. Studies on rodents claim that FGF16 also has a regulatory effect on bile acid metabolism [ 49 ]. However, in birds, the role of FGF19 in retinal development and that of FGF16 in inner ear development have been reported [ 50 , 51 ], whereas research on the functions of FGF19 and FGF16 in the gut is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 is mainly secreted by ileal enterocytes in response to bile acid activation of the nuclear receptor FXR, and then, FGF19 acts on the cell surface receptor complex in hepatocytes to inhibit bile acid synthesis and gluconeogenesis and stimulate glycogen protein synthesis [ 48 ]. Studies on rodents claim that FGF16 also has a regulatory effect on bile acid metabolism [ 49 ]. However, in birds, the role of FGF19 in retinal development and that of FGF16 in inner ear development have been reported [ 50 , 51 ], whereas research on the functions of FGF19 and FGF16 in the gut is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, Bex1, Apln, kcne1l, Med12, Dad1, and Fgf16 were significantly upregulated in the liver or brain at the torpor stage (Figure 4D), suggesting their involvement in both hibernation and plateau adaptation. Previous studies have reported that these genes are involved in many physiological processes, including neuronal differentiation, liver regeneration, angiogenesis, and energy metabolism (Yu et al., 2016, Gu et al., 2018, Wysocka et al., 2018, Vilar et al., 2006, He et al., 2015, Rulifson et al., 2017). Further experimental validation is needed in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mice overexpressing FGF16 delivered by adeno-associated virus display dramatic weight loss and uncoupling protein-1 (UCP1) upregulation in inguinal white adipose tissue (WAT), which is a common site for emergent active brown adipose tissue (BAT). These effects are likely a combined result of reduced food and water intake and abnormal feces replete with lipid and bile acid due to the brain, liver, and intestinal actions of overexpressed FGF16 [45]. Mice deficient in FGF1 exhibit insignificant phenotypes under standard dietary conditions; however, under a chronic high-fat diet, these mice develop an aggressive diabetic phenotype coupled with aberrant adipose phenotypes, including multiple histopathologies in the adipose vasculature network, accentuated inflammatory response, aberrant adipocyte size distribution and expansion, and ectopic expression of pancreatic lipases [46].…”
Section: The Mitogenic Fgf Axismentioning
confidence: 99%